2022
DOI: 10.1159/000521242
|View full text |Cite
|
Sign up to set email alerts
|

Lean Mass Loss and Altered Muscular Aerobic Capacity after Bariatric Surgery

Abstract: <b><i>Introduction:</i></b> Patients undergoing weight loss surgery do not improve their aerobic capacity or peak oxygen uptake (VO<sub>2</sub>peak) after bariatric surgery and some still complain about asthenia and/or breathlessness. We investigated the hypothesis that a post-surgery muscular limitation could impact the ventilatory response to exercise by evaluating the post-surgery changes in muscle mass, strength, and muscular aerobic capacity, measured by the first venti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Despite these benefits, the surgery associated energy deprivation also leads to significant decreases in muscle mass. This might negatively affect whole-body metabolism such as aerobic capacity [ 62 ], regulation of resting metabolic rate, and possible lead to long-term musculoskeletal issues [ 63 ]. Of note, muscle mass losses in adolescents have been associated with an increased risk of metabolic syndrome [ 64 ] and nonalcoholic fatty liver disease development [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite these benefits, the surgery associated energy deprivation also leads to significant decreases in muscle mass. This might negatively affect whole-body metabolism such as aerobic capacity [ 62 ], regulation of resting metabolic rate, and possible lead to long-term musculoskeletal issues [ 63 ]. Of note, muscle mass losses in adolescents have been associated with an increased risk of metabolic syndrome [ 64 ] and nonalcoholic fatty liver disease development [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weight loss predicts lean mass loss 22 . Where patients lose substantial weight such as post bariatric surgery or in response to anti‐obesity medication, lean mass loss may go on to negatively impact upon function 23–25 . Furthermore lean mass loss may increase the likelihood of weight regain 26 .…”
Section: Optimizing Weight Loss Quality and Weight Loss Maintenancementioning
confidence: 99%
“…22 Where patients lose substantial weight such as post bariatric surgery or in response to anti-obesity medication, lean mass loss may go on to negatively impact upon function. [23][24][25] Furthermore lean mass loss may increase the likelihood of weight regain. 26 While exercise does not significantly enhance weight loss, evidence shows aerobic exercise and higher levels of physical activity are therapeutically relevant to positively influence weight loss maintenance.…”
Section: Optimizing Weight Loss Quality and Weight Loss Maintenancementioning
confidence: 99%
“…Although previous studies have demonstrated low HRV in obesity and sarcopenia [ 4 , 5 , 6 , 7 ] and that bariatric surgery (BS) reduced blood pressure (BP) and cardiac autonomic dysfunction in patients with obesity [ 14 , 15 , 16 , 17 ], there are no data in the literature evaluating the impact of BS on cardiac autonomic modulation in individuals with parameters related to sarcopenia. Considering the probable loss of muscle mass after BS [ 18 ] and that irisin, a myokine that acts in neurons in the nucleus as ambiguous promoting bradycardia, is produced by skeletal muscle, it is reasonable to infer that the benefits of BS on the cardiac autonomic system might be attenuated in individuals with low muscle mass and strength. [ 19 ].…”
Section: Introductionmentioning
confidence: 99%